In vitro evaluation of the α-glucosidase inhibitory potential of methanolic extracts of traditionally used antidiabetic plants - Astha Bhatia; Balbir Singh; Rohit Arora; Saroj Arora (BMC, 2019)
Abstract Background Different plant parts of Roylea cinerea (D. Don) Baill. (Lamiaceae), Clematis grata Wall. (Ranunculaceae), Cornus capitata Wall. (Cornaceae) are traditionally used in the management of diabetes and various other diseases. Method The air-dried plant parts from different plants were coarsely powdered and macerated in methanol to obtain their crude extracts. The crude extracts were evaluated for their α-glucosidase inhibitory activity. On the basis of results obtained, the methanolic crude extract of Cornus capitata Wall. was further sequentially fractionated in hexane, diethyl ether, ethyl acetate, n-butanol. Fractions obtained were also evaluated for their α-glucosidase inhibitory potential. The kinetic study was performed using Lineweaver Burk plot to evaluate the type of inhibition. Furthermore, in silico analysis was also carried with active sites of the enzyme (PDB ID: 3WY1) using Autodock4. Results Among all the plant extracts, Cornus capitata extract showed maximum inhibitory activity. Therefore its methanolic extract was further fractionated with the help of different solvents and the maximum activity was shown by the ethyl acetate fraction (IC50 50 μg/mL). Kinetic analysis indicated that Vmax and Km were increased indicating a competitive type of inhibition. In docking studies, among different constituents known in this plant, betulinic acid showed minimum binding energy (− 10.21 kcal/mol). The kinetic and docking studies have strengthened the observation made in the present study regarding the α-glucosidase inhibitory activity of Cornus capitata. Conclusion The study provided partial evidence for pharmacological basis regarding clinical applications of Cornus capitata in the treatment of diabetes suggesting it to be a suitable candidate for the treatment of postprandial hyperglycemia.